Pengaruh Penggunaan Model Pembelajaran Problem Based Learning (PBL) dan Perhatian Orang Tua Terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas VII SMP Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2025/2026 - Siahaan Sumingse; Andar Gunawan Pasaribu; Baginda Sitompul (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The purpose of this study was to determine 1) the positive and significant influence of the use of the Problem Based Learning (PBL) Learning Model on the learning activity of Christian Religious Education (PAK) and Character Education of class VII students of SMP Negeri 1 Sipoholon, North Tapanuli Regency in the 2025/2026 Academic Year; 2) the positive and significant influence of parental attention on the learning activity of Christian Religious Education (PAK) and Character Education of class VII students of SMP Negeri 1 Sipoholon, North Tapanuli Regency in the 2025/2026 Academic Year; and 3) the positive and significant influence of the use of the Problem Based Learning (PBL) Learning Model and parental attention together on the learning activity of Christian Religious Education (PAK) and Character Education of class VII students of SMP Negeri 1 Sipoholon, North Tapanuli Regency in the 2025/2026 Academic Year. The method used in this study is the inferential quantitative method. The population was all 160 students of Class VII of SMP Negeri 1 Sipoholon, North Tapanuli Regency, in the 2025/2026 academic year, and a sample of 80 people was determined using random sampling techniques. The instrument trial was conducted on 35 students of Class VII of SMP Negeri 1 Sipoholon, North Tapanuli Regency, Academic Year 2025/2026 outside the research sample so that it was known that of the 66 questionnaire items tested, 64 research instruments were declared valid and reliable because they had met the validity and reliability value criteria. The results of the data analysis showed that: 1) the Fcount value > Ftable, namely 31.510 > 3.15, thus it was known that there was a positive and significant influence of the use of the problem based learning (PBL) learning model on partial learning activity. The influence was 28.8%, 2) the Fcount value > Ftable, namely 28.741 > 3.15, thus it was known that there was a positive and significant influence of parental attention on partial learning activity. The influence is 26.9%, and 3) the calculated Fvalue > Ftable is 22.166 > 3.15, thus it is known that there is a positive and significant influence of the use of the problem-based learning model (PBL) and parental attention on learning activity simultaneously. The influence is 36.5%, thus Ha is accepted and H0 is rejected